Increasing prevalence of myopia and the impact of education in primary-school students in Xi'an, north-western of China - Ye, Lu; Yang, Yan-qi; Zhang, Guo-yun; Wang, Wen-jun; Ren, Mei-xia; Ge, Pan; Zhang, Jian; Zhang, Nan; Liu, Xing-zhou; Zhang, Ming-lei; Tong, Yu-jiao; Lu, Liang-cai; et al. (Frontiers in Public Health, 2022)
Purpose The present study was performed to detect the prevalence of myopia among primary-school students in Xi’an, north-western of China. Methods The present study was a school-based study with students aged from 6 to 13 years old. All the individuals underwent ophthalmological examination and spherical equivalent (SE) of refractive error were measured with non-cycloplegic refraction. Myopia was defined as a SE of ≤-0.5 diopters (D), and further divided into three stratified groups based on SE: low myopia (≤−0.5D to >−3.0D), moderate myopia (≤−3.0D to >−6.0D), and high myopia (≤−6.0D). Relative risk factors, including age, sex, grade and ethnicity were investigated using questionnaire. Results A total of 4680 individuals were eligible for this survey and 4654 (99.4% participation rate) were finally included (51.2% boys). The mean age of participants was 8.756 ± 1.727 years. The whole city-level prevalence of total myopia was 57.1% (95%CI: 55.7%-58.6%). Additionally, the prevalence of low, moderate, and high myopia was 45.0% (95%CI: 43.5%-46.4%), 11.1% (95%CI: 10.2%-12.0%), and 1.0% (95%CI: 0.7%-1.3%), respectively. Moreover, grade (education level) instead of age, sex and ethnicity was the most essential risk factor for prevalence of overall myopia (OR=1.844, 95%CI: 1.605-2.119), and an increase of prevalence by 84.4% per grade was seen. Furthermore, similar associations of grade were significant with low myopia (OR=1.613, 95%CI: 1.385-1.877) and moderate myopia (OR=2.186, 95%CI: 1.693-2.823), meanwhile, prevalence of low myopia and moderate myopia demonstrated an increase of prevalence by 61.3% and 118.6% per grade, respectively. None of the factors included in the present study was significant risk factor for high myopia. Conclusions The present study investigated a non-negligible high prevalence of myopia among primary-school students in Xi’an, north-western of China, and a gradual increasing in proportion with education level.